(untitled) (Scientific electronic journal "Labor Economics and Human Capital", 2025)
The article examines the theoretical views of foreign economists who conducted scientific research in this area, based on the essence of entrepreneurial activity and the need for professional training of the population. The formation and development of the system of entrepreneurial education in economically developed countries, as well as the mechanism for training personnel in it, are deeply analyzed. In addition, based on the experience of successfully developed countries of the USA and Europe, possible directions for the development of professional training of personnel for entrepreneurship in the education system of Uzbekistan are proposed.